Time and sequence of eruption of permanent teeth in Ankara, Turkey. Issue 1 (April 2016) - Oznurhan, Fatih; Ekci, Elif Sungurtekin; Ozalp, Serife; Deveci, Ceren; Delilbasi, Aslı Evren; Bani, Mehmet; Oztas, Nurhan
Abstract: Introduction: The aim of this study was to determine time and sequence of eruption of permanent teeth in addition to caries status and gender differences in children and young adolescents in Ankara. Materials and methods: Cross-sectional data were collected by examining a total of 890 (407 female and 483 male) pre-school, primary and secondary school children of 5–15 years of age. The mean age of eruption and caries status of individual permanent teeth were recorded. Data were statistically evaluated with sample T-Test and One-way ANOVA. Results: Eruption tended to be earlier in girls than boys in most of the groups accept for the teeth 44. The sequences of eruption of permanent teeth were 6-1-2-4-3-5-7 in mandible, and 6-1-2-4-5-3-7 in maxilla in boys whereas 1-6-2-3-4-5-7 in mandible, and 6-1-2-5-4-3-7 in maxilla in girls. Increased caries prevalence was seen both in primary and permanent teeth. Conclusion: When compared with the other studies, eruption times show differences which were affected by genetics, genders, ethnicity, nutrition, fluoridation, carious condition, premature extraction of predecessors, socioeconomic variables, congenital anomalies and the changes in eruption time is significant when planning dental treatments.